Sinergitas Guru dan Orangtua Dalam Membentuk Karakter Disiplin dan Rasa Hormat Peserta Didik - Mahbubi, M; Husein, Shofiyah (CENDEKIA, 2023)
The most important component of success in education is through the synergy of teachers and parents. In reality, in every lesson at school or outside of school, teachers need synergy from parents of students. Therefore, the researcher intends to examine the form of the synergy between teachers and student guardians regarding discipline and respect for MTs students. Al-Husna Dawuhan Krejengan Probolinggo. This research uses a type of qualitative research where the types of data are in the form of observations, interviews, and documentation and uses two data, namely primary and secondary data. The conclusions from this study include: (1) Holding meetings at each grade level to disseminate information about school rules, (2) Establishing a good form of interaction between teachers and student guardians, (3) Teaching students to be able to manage time well, ( 4) Establishing harmony and setting a good example to students, (5) Making reports related to the development of student behavior at school and home, (6) Providing time breaks for students who violate the rules at school and at home.